Circulating microparticles and plasma levels of soluble E- and P-selectins in patients with systemic sclerosis. (November 2013) - Iversen, LV; Østergaard, O; Ullman, S; Nielsen, CT; Halberg, P; Karlsmark, T; Heegaard, NHH; Jacobsen, S
<x xml:space="preserve">Abstract</x> Objectives: Microparticles (MPs) may be involved in the pathogenesis of systemic sclerosis (SSc), which includes vasculopathy, endothelial cell activation, and coagulation activation. Circulating MPs from SSc patients were characterized and their relationship with soluble markers of vascular activation investigated. Method: This study included 121 SSc patients [79 with limited (lcSSc) and 42 with diffuse cutaneous SSc (dcSSc)] and 49 sex- and age-matched healthy controls (HCs). The MPs were characterized by flow cytometry for annexin V (AnxV)-binding capacity and their expression of surface markers of platelets (PMPs), leucocytes (LMPs), or endothelial cells (EMPs). Plasma levels of soluble (s) E- and P-selectins were determined by enzyme-linked immunosorbent assay (ELISA). Results: The total concentrations of MPs and of PMPs, LMPs, and EMPs were 22−42% lower in SSc patients than in HCs (p < 0.001). However, within the cell-derived MP pool, a 47% higher fraction of AnxV non-binding MPs (F-AnxV− MPs) was found in the SSc patients compared to the HCs (p < 0.05). The plasma levels of sE- and sP-selectins were increased by 47−64% in the SSc patients compared to HCs (p < 0.001). Multiple regression analysis showed that the raised plasma levels of sE- and sP-selectin were associated with F-AnxV– EMPs in dcSSc patients (p = 0.008 and p = 0.001, respectively) but not in lcSSc patients (p = 0.33 and p = 0.82, respectively). Conclusions: While the total number of MPs was decreased, the number of F-AnxV– MPs increased in SSc patients. The F-AnxV– EMPs were associated with plasma levels of markers of vascular activation in patients with dcSSc.